Detection of Quinolone Antibiotics by Magnetic Solid-Phase Extraction Coupled with High-Performance Liquid Chromatography Based on Graphene-Conjugated Porous Materials - Bacher, Gerson; Clavijo, Ricardo; Alves, Navadol (Journal of Green Energy and Environmental Engineering, 2026)
An analytical methodology was established for simultaneous determination of four banned quinolone residues through magnetic solid-phase extraction coupled with high-performance liquid chromatographic separation. The extraction sorbent comprised a graphene-derived composite porous architecture (Fe₃O₄@CMP-2). The conjugated microporous polymer precursor (CMP-1) was fabricated via Sonogashira cross-coupling polymerization employing 1,3,5-triethynylbenzene and 4,4'-dibromobiphenyl-2,2'-diamine as comonomers. Subsequently, CMP-2 was prepared by condensing CMP-1 with graphene oxide (GO). The resulting CMP-2 was subjected to systematic structural and morphological characterization. A mixed MSPE adsorbent was prepared via simple physical mixing of CMP-2 and nano-Fe3​O4 to separate and enrich the four quinolone drugs in food and water samples. Single-factor experiments were conducted to examine the key parameters affecting extraction performance. Under optimized analytical conditions, the developed approach exhibited robust linear response across the 0.050–20.00 μg/L calibration range, with determination coefficients exceeding 0.9961. Method sensitivity, expressed as limits of detection, spanned 0.004–0.022 μg/L. Accuracy assessment via tri-level fortified recovery trials yielded extraction efficiencies between 97% and 118%, with precision characterized by relative standard deviations of 0.02%–2.3%. Compared with similar enrichment methods reported in the literature, this method offers distinct advantages across multiple dimensions: a smaller sample volume, less adsorbent material, short extraction and desorption times, and simpler operation.